Rational Design of Coplanar Polypyrrole‐Based Graphene Hydrogels with Excellent Energy‐Storage Performance. Issue 11 (6th September 2021) - Ding, Jiannan; Chen, Peng; Wang, Bin; Chen, Xuli; Guo, Kunkun
Abstract : Polypyrrole‐based graphene hydrogels (PGRs) are promising candidates for supercapacitor electrodes adapted to portable and wearable energy‐storage devices. A self‐assembly strategy is developed to fabricate PGR hydrogels by PPy@GO powders, which are in situ‐polymerized pyrrole monomers in aqueous GO solutions. The oxygen‐containing function groups of GO can provide rich active sites to induce polymerization, and the interactions between GO and polypyrrole are conductive to enhancing the dispersibility of PPy. Likewise, the structural characterizations and DFT calculations demonstrate that PPy chains polymerized in such a way can easily form the coplanar PPy structure via α−α connection together with better conductivity. As such, PGR hydrogel electrode has an ultrahigh specific capacitance of 631 F g −1 at 1 A g −1, approximately twice more than pristine PPy (284.7 F g −1 ). Even with the current density increase up to 20 A g −1, PGR still maintains a capacitance retention rate of 84.1%, but pristine PPy is only 33%. In addition, the flexible all‐solid‐state supercapacitor assembled based on PGR and RGO hydrogel electrodes can achieve a high cycle stability of 91.3% after 3000 cycles. These results obviously open interesting perspectives of PPy‐based graphene hydrogels to become an advanced flexible power device. Abstract : A self‐assemble strategy is adopted to fabricate coplanar polypyrrole‐based graphene hydrogels. This hydrogel electrode exhibits ultrahigh specific capacitance (631 F g −1 at 1 A g −1 ) and excellent rate performance (84.1% at 1−20 A g −1 ). In addition, the assembled flexible asymmetric all‐solid‐state supercapacitors exhibit high cycle stability (91.3%, 3000 cycles).